1980
DOI: 10.1177/014107688007300909
|View full text |Cite
|
Sign up to set email alerts
|

Acute Abdominal Pain in Children

Abstract: During a twelve-month period, 416 children with acute abdominal pain required emergency admission to Southampton General Hospital; 46% had operations. Appendicitis was the commonest organic cause of acute abdominal pain identified (31%). Constipation (9%) can present as acute abdominal pain simulating appendicitis. All children should have a urine sample examined microscopically and the finding of significant pyuria is suggestive, but not diagnostic, of a urinary tract infection (7%). Mesenteric adenitis, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We believe that constipation in the ED is in most cases a result of a shortage of dietary fiber or fluids or simply idiopathic constipation, and classification as simple constipation is justified. The relatively high incidence of constipation, 19%, at our center compared with 5% to 11% in most of the literature (11–14) may be a result of the reluctance of other physicians to view constipation as a diagnosis. Loening‐Baucke and Swidsinski found constipation to be responsible for 48% of cases of acute abdominal pain in their pediatric population in a primary health care setting (15).…”
Section: Discussionmentioning
confidence: 62%
“…We believe that constipation in the ED is in most cases a result of a shortage of dietary fiber or fluids or simply idiopathic constipation, and classification as simple constipation is justified. The relatively high incidence of constipation, 19%, at our center compared with 5% to 11% in most of the literature (11–14) may be a result of the reluctance of other physicians to view constipation as a diagnosis. Loening‐Baucke and Swidsinski found constipation to be responsible for 48% of cases of acute abdominal pain in their pediatric population in a primary health care setting (15).…”
Section: Discussionmentioning
confidence: 62%
“…Two patients died (mortality rate 1.5%). At the Guys Hospital, 46% of the children were operated (8) while in the Central African study 50% of the children seen with acute abdominal pain underwent surgery (7,9).…”
Section: Resultsmentioning
confidence: 99%
“…The main conditions requiring surgical intervention in this study compares well with the Central African study which found appendicitis to contribute to 32.4%, hernia 4.8% and typhoid perforation 9.9% (7). Appendicitis in the Guys hospital study contributed to 31%, constipation 9%, but at the Princess Margaret Hospital for children in Australia, 74% of the children undergoing surgery were found to have appendicitis (8,9). The Aus- (14).…”
Section: Discussionmentioning
confidence: 98%
“…2). The mean Alvarado score in the group 1 was 7.9 (range, 6-10) where as in those operated later than 12 hours (group 2), it was 4.5 (range, [3][4][5][6][7][8].…”
Section: Resultsmentioning
confidence: 99%
“…It is common practice to admit and observe patients with an uncertain diagnosis of acute appendicitis. This has been known to avoid unnecessary appendectomies as well as correctly identify those cases ORIGINAL ARTICLE whose diagnosis at presentation was uncertain [4][5][6][7][8]. The delay in surgery, in theory, increases the chances of complications in the peri-operative period; but it has been shown that delay in the patient presentation is the main contributing factor in development of complications rather than delay at the physician's end [8].…”
Section: Introductionmentioning
confidence: 99%